Tika technology: an alternative blueprint for digitalisation. (7th April 2023) - Munn, Luke
Abstract : Digitalisation has the capacity to radically transform the nature of work, redefining tasks, requirements and remuneration. Yet technologies have often been used to reduce worker autonomy, exacerbate racial and gendered inequality and intensify labour precarity. How can digitalisation instead support emancipatory labour conditions? This article introduces the concept of 'tika technology', drawing together scholarship on convivial tools, appropriate technology and calm computing to theorise its purposes and principles. To illustrate what these look like in practice, the article provides two real-world examples of tika technology. It concludes by exploring potential benefits at the individual, societal and environmental levels.